Kualitas Pelayanan Program Denpasar Mantap Kesehatan Masyarakat (Damakesmas) di Kota Denpasar - Wahyuni, Komang Tatik; Winaya, I Ketut; Yasintha, Putu Nomy (CITIZEN CHARTER, 2021)
The Public in Denpasar town needs public service outside of the health building, from the decree of mayor number 188.45/84/HK/2019. Damakesmas Program has two programs are SPGDTS is a service of pre-hospital, and Perkesmas is a home care service. The purpose of this research is to know about the quality of the service Damakesmas Program which is given to the public as part of service outside health building. The Document is collected with the method of a semi-structured interview, observations, and documentation. Based on research used theory of Service Quality from Zeithaml-Passuraman-Berry which has five indicators that affect the quality of services such as Tangibles, Reliability, Responsiveness, Assurance, and Empathy indicator. The result of the research show service quality Damakesmas Program already undergone with good enough but it was still found problem such as the service is not correct from the target and it happens service rejection from the public. Keyword: Service Quality, Damakesmas Program, Health